OPTIMIZATION OF BANDWIDTH MANAGEMENT WITH SIMPLE QUEUE LIMITATION USING MIKROTIK DEVICES IN SUKARAJAKULON VILLAGE - Nafa Nandi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Optimization is an effort to improve an activity or job in order to minimize losses or maximize profits in order to achieve the best possible goals within certain limits. The aim of this research is to be able to make efforts to use devices such as computers, internet access so that they can be used more optimally. In this case, there is still less than optimal use of computers due to limited internet access in certain rooms, therefore this research is able to answer and provide benefits. The research methods used are literature studies and field studies. The data analysis used is descriptive analysis including analysis of the current system, analysis of hardware and software requirements. The results obtained were the addition of 2 access points, 100 meters of UTP cable, 1 unit of switch hub, and 1 unit of proxy. Such as the division of bandwidth management for computers UpTo 40 Mbps, special Ap UpTo 40 Mbps, and Ap for guests 10 Mbps. The conclusion obtained is that by placing the access point in the right area, the WLAN network will be optimal. Based on the results of the questionnaire, it was stated that use was more optimal and the difference was very noticeable